Prognostic relevance of preoperative CA 19-9 values in stage III rectal adenocarcinoma: retrospective analysis and clinical implications - Edin Hodžić; Sadat Pušina; Adi Mulabdić; Mirhan Salibašić; Emsad Halilović; Mujo Kadrić (Medicinski glasnik, 2024)
Aim: To investigate prognostic significance of preoperative levels of the Carbohydrate anti-gen 19-9 (CA 19-9) in patients with stage III rectal adenocarcinoma who underwent a treatment at the Clinical Centre of the University of Sarajevo. Methods: A retrospective cohort study included 84 patients who underwent radical anterior rectal resection due to grade III rectal adenocarcinoma, followed by adjuvant chemotherapy according to the FOLFOX protocol (Oxaliplatin, Leucovorin, 5-Fluorouracil (5-FU)). The patients were divided into two groups according to CA 19-9 values (?27 U/mL and <27 U/mL, respectively). Results: High pre-operative CA 19-9 values predicted an increased probability of postoperative metastases, especially liver, lung and abdominopelvic metastases, as well as three-year disease-free survival (3Y-DFS) and three-year overall survival (3Y-OS). The 3Y-DFS rate for patients with high CA 19-9 was 64.5%, while for those with low CA 19-9 it was 87.2%. The 3Y-OS rate for patients with high CA 19-9 was 89.8%, while for those with low CA 19-9 it was 65.7%. Univariate and multivariate regression analysis confirmed that a high level of CA 19-9 is an independent predictor for DFS and OS shorter than three years. Conclusion: Pre-operatively elevated values of CA 19-9 in rectal adenocarcinoma have a significant role in predicting the outcome in patients with stage III rectal adenocarcinoma.
Keywords: biomarkers; colo-rectal surgery; neo-plasms; patient out-come assessment